Fibroblast Growth Factor 2-A Review of Stabilisation Approaches for Clinical Applications - Leah Benington; Gunesh Rajan; Cornelia Locher; Lee Yong Lim (MDPI AG, 2020)
Basic fibroblast growth factor (FGF)-2 has been shown to regulate many cellular functions including cell proliferation, migration, and differentiation, as well as angiogenesis in a variety of tissues, including skin, blood vessel, muscle, adipose, tendon/ligament, cartilage, bone, tooth, and nerve. These multiple functions make FGF-2 an attractive component for wound healing and tissue engineering constructs; however, the stability of FGF-2 is widely accepted to be a major concern for the development of useful medicinal products. Many approaches have been reported in the literature for preserving the biological activity of FGF-2 in aqueous solutions. Most of these efforts were directed at sustaining FGF-2 activity for cell culture research, with a smaller number of studies seeking to develop sustained release formulations of FGF-2 for tissue engineering applications. The stabilisation approaches may be classified into the broad classes of ionic interaction modification with excipients, chemical modification, and physical adsorption and encapsulation with carrier materials. This review discusses the underlying causes of FGF-2 instability and provides an overview of the approaches reported in the literature for stabilising FGF-2 that may be relevant for clinical applications. Although efforts have been made to stabilise FGF-2 for both in vitro and in vivo applications with varying degrees of success, the lack of comprehensive published stability data for the final FGF-2 products represents a substantial gap in the current knowledge, which has to be addressed before viable products for wider tissue engineering applications can be developed to meet regulatory authorisation.